CORRELATION BETWEEN LEARNING STYLES AND LEARNING OUTCOMES IN DENTISTRY STUDENTS - Nabila Maulida; Cicih Bhakti Purnamasari; Sulistiawati Sulistiawati; Riries Choiru Pramulia Yudia; Endang Sawitri (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2025)
Background: Learning style represents one of the key elements that shape how effectively personals acquire knowledge and skills. A clear understanding of these styles plays a critical role in enhancing a learner’s ability to comprehend, process, and retain information, thereby supporting the optimisation of instructional strategies. By recognising the diversity of learning preferences, educators can design and implement teaching approaches that are more responsive to learners’ unique needs, ultimately leading to improved educational outcomes.Objecties: This study examined the connection among learning styles and academic performance among dental students enrolled in the Faculty of Medicine at Mulawarman University. Method: This study employed a quantitative approach by a cross-sectional research design. A total of 106 dentistry students by the Faculty of Medicine, Mulawarman University, participated as participants. Data collection was carried out utilizing the ARK (Visual, Auditory, Read/Write, and Kinesthetic) Learning Styles Questionnaire. The data obtained were subsequently processed and analyzed through univariate analysis utilizing frequency distribution and bivariate analysis utilizing the Kruskal–Wallis test. Results: The outcomes drew that the predominance of participants demonstrated a kinesthetic learning style (64.4%) and achieved good academic performance (97%). The bivariate analysis examining the connection among learning style and learning outcomes indicated a p-value of 0.805 (p > 0.05), recommending no statistically substantial association among the two variables. Conclusion: It can be outlined that there is no statistically substantial connection among learning style and academic performance among dentistry students at the Faculty of Medicine, Mulawarman University.